Analysis of the transcription process in the writing of deaf students - Gutiérrez Cáceres, Rafaela (Revista Complutense de Educación, 2012)
This paper analyzes the skills that they have deaf students of secondary education in the knowledge and use of the cognitive transcription process. For data collection, has carried out a “cognitive interview”, after spontaneous writing an essay of narrative text. Subsequently has applied the content analysis of interviews and written texts according to a categories ranking system that has been validated with the procedure of “experts´ judgment”. In the analysis of results has been found that, in general, deaf students of secondary education do not have the skills needed to express ideas in writing properly, using correct language structure and form of the text. In any case, it should be noted that there is variability among deaf students depending on their individual and contextual characteristics.